Impact of real-time elastography on magnetic resonance imaging/ultrasound fusion guided biopsy in patients with prior negative prostate biopsies - Brock, Marko; Pelzer, Alexandre E. (The journal of urology, 2015)
Purpose: The fusion of multiparametric resonance imaging and ultrasound has been proven capable of detecting prostate cancer in different biopsy settings. The addition of real-time elastography promises to increase the precision of the outcome of targeted biopsies. We investigated whether real-time elastography improves magnetic resonance imaging/transrectal ultrasound fusion targeted biopsy in patients after previous negative biopsies. Materials and Methods: Prospectively 121 men underwent 3T magnetic resonance imaging. Using magnetic resonance imaging/real-time elastography fusion every suspicious lesion was characterized according to its tissue density and sampled by 2 fusion guided targeted biopsies. Additionally, all patients underwent 12-core systematic biopsy. The detection rate of clinically significant and insignificant cancers was compared between targeted und systematic biopsies. The accuracy to predict high grade prostate cancer was evaluated for with the PI-RADS scoring system and compared to the magnetic resonance imaging/real-time elastography fusion score. Results: Overall prostate cancer was detected in 52 patients (43%). Targeted fusion guided biopsy revealed prostate cancer in 32 men (26.4%) and systematic biopsy in 46 (38%). The proportion of clinically significant cancers was higher for targeted biopsy (90.6%) compared to systematic biopsy (73.9%). The detection rate per core was higher for targeted biopsies (14.7%) compared to systematic biopsies (6.5%, p <0.001). The prediction of biopsy result according to magnetic resonance imaging/real-time elastography fusion was better (AUC 0.86) than magnetic resonance imaging alone (AUC 0.79). Sensitivity and specificity for magnetic resonance imaging/real-time elastography fusion was 77.8% and 77.3% vs 74.1% and 62.9% for magnetic resonance imaging. Conclusions: Magnetic resonance imaging/transrectal ultrasound fusion enhances the likelihood of detecting clinically significant cancers in a repeat biopsy setting. Adding real-time elastography to magnetic resonance imaging supports the characterization of cancer suspicious lesions.
Gesehen am 04.12.2018